The Impact of Dissolved Nitrate and Phosphate on Maximum Growth Rate and Carrying Capacity of Oscillatoria in Intensive Shrimp (Litopenaeus vannamei) Farming Pond Situbondo, East Java, Indonesia - Aliviyanti, Dian; Suharjono, Suharjono; Retnaningdyah, Catur (The Journal of Experimental Life Science, 2017)
The aims of study are to analyze the effect of dissolved nitrate and phosphate content of the intensive shrimp farming pond Situbondo to maximum growth rate and carrying capacity of Oscillatoria population density in the laboratory. This is an experimental research method using completely randomized design with three replications. The treatment were variation of nitrate and phosphate concentration (N0; N6; N12; N24; N48; P0,2; P0,4; P0.8, P1.6  mg.L-1).  Experiment was done using a pure Oscillatoria culture in condition 25 watt lamp; 12 hours a day. The initial amount of Oscillatoria cells used for the treatment is 8 - 15 x 104 cell.mL-1. During the incubation process, chemical parameters were also observed including nitrate, phosphate, DO, and pH at the beginning of the incubation period. Oscillatoria cell was count every day until stationary phase for 30 days. Furthermore, a different test between treatments was conducted to determine levels of nitrate and phosphate in triggering the blooming of Oscillatoria using Oneway ANOVA analysis with SPSS Program. The results showed that the intensive shrimp pond waters of Situbondo already contain dissolved phosphate between 0.4 - 0.5 mg.L-1. Oscillatoria growth is strongly influenced by dissolved phosphate content in waters, phosphate levels of 0.2 - 0.4 or equivalent to the actual level of 0.6 - 0.7 mg.L-1 can cause the highest abundance of Oscillatoria that could endanger the ecosystem.  Keywords: dissolved phosphate, intensive shrimp farming, Nitrate, Oscillatoria.